2015
DOI: 10.1209/0295-5075/111/28002
|View full text |Cite
|
Sign up to set email alerts
|

A modified Poisson-Boltzmann theory: Effects of co-solvent polarizability

Abstract: -In this paper within a field-theoretical approach taking into account explicitly a cosolvent with a nonzero dipole and a polarizability tensor, we derive a modified Poisson-Boltzmann equation. Applying the modified Poisson-Boltzmann equation, we formulate a generalized GouyChapman theory for the case when an electrolyte solution is mixed with a polar co-solvent having a large polarizability. We show that an increase of the co-solvent concentration as well as the co-solvent polarizability lead to a significant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…The latter is one of the most important quantities for the electrochemical applications. In a recent work 26 we showed in the framework of the field-theoretical approach that if an electrolyte solution is mixed with some strongly polarizable dielectric co-solvent, then the variation of the differential capacitance becomes the greater the stronger polarizability grows.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is one of the most important quantities for the electrochemical applications. In a recent work 26 we showed in the framework of the field-theoretical approach that if an electrolyte solution is mixed with some strongly polarizable dielectric co-solvent, then the variation of the differential capacitance becomes the greater the stronger polarizability grows.…”
Section: Introductionmentioning
confidence: 99%
“…and renormalized dielectric permittivity 76,77 ε r (r) = ε(r) + 4πp 2 3k B T n m (r) (20) have been introduced.…”
Section: Appendix: Derivation Of Electrostatic Free Energy (4)mentioning
confidence: 99%
“…Experimental , theoretical , and computational studies have shown that ionic liquids exhibit the finite‐size (crowding or steric) effects of ions and electrostatic correlations (overscreening effects). Efforts have been made to capture these effects, especially on the structure and capacitance of electric double layer (EDLs) for ionic liquids .…”
Section: Introductionmentioning
confidence: 99%